New insights on the subsidence of Lipari island (Aeolian islands, southern Italy) from the submerged Roman age pier at Marina Lunga. (16th May 2016) - Anzidei, Marco; Bosman, Alessandro; Casalbore, Daniele; Tusa, Sebastiano; La Rocca, Roberto
Abstract: Lipari island belongs to the Aeolian archipelago, located in the Southern Tyrrhenian Sea (Italy), which is one of the most active volcanic areas of the Mediterranean basin. Although this region has been settled since prehistory, only during Roman times were coastal installations built in these islands. In this study, we present and discuss data on the relative sea level change estimated from a submerged pier of Roman age dated 2100 ± 100 BP. This structure, about 140 × 60 m, is located along the coast of Marina Lunga, corresponding to the present location of the main harbor of Lipari island. This pier, which was accidentally discovered in 2008 during preliminary excavations for the construction of a new pier, is a valuable indicator of relative sea level changes and vertical land movements. Its top surface is presently located at −9.1 ± 0.05 m, while the foundations at the outer end of the pier are at −11.6 ± 0.05 m, above a shoreline placed at −13.0 ± 0.05 m. We studied this site through direct archaeological investigations and ultra-high resolution multibeam bathymetry. The current submergence of this pier can be explained by the cumulative effect of the relative sea level changes caused by the regional glacio-hydro-isostatic signal, active since the end of the last glacial maximum, and the local volcano-tectonic land subsidence. From our investigations, a relative sea level change at 12.3 ± 0.7 m with a subsidence rate at 5.79 ± 0.01 mm y −1 and an average value of volcano-tectonic contribution at 5.17 ± 0.01 m y −1 for the last 2100 ± 100 years BP, is estimated from comparison against the latest predicted sea level model for the Southern Tyrrhenian Sea. These rates of relative sea level change led to the disuse of the harbor after around the fourth century AD, in agreement with archaeological interpretations. Our results provide new insights on the recent evolution of this active volcanic area.